2014
DOI: 10.1021/ja509348t
|View full text |Cite
|
Sign up to set email alerts
|

Unification of Catalytic Water Oxidation and Oxygen Reduction Reactions: Amorphous Beat Crystalline Cobalt Iron Oxides

Abstract: Catalytic water splitting to hydrogen and oxygen is considered as one of the convenient routes for the sustainable energy conversion. Bifunctional catalysts for the electrocatalytic oxygen reduction reaction (ORR) and the oxygen evolution reaction (OER) are pivotal for the energy conversion and storage, and alternatively, the photochemical water oxidation in biomimetic fashion is also considered as the most useful way to convert solar energy into chemical energy. Here we present a facile solvothermal route to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
427
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 597 publications
(455 citation statements)
references
References 121 publications
20
427
0
Order By: Relevance
“…On the CoP and a‐CoOx nanointerfaces, the OH − could preferentially attach to a a‐CoOx site at the interface due to strong electrostatic affinity to the locally positively charged Co 2+ /Co 3+ species and more empty d orbitals in Co 2p than that in CoP, while a nearby CoP site would facilitate H adsorption; suggesting synergistic electrocatalytic activity to CoP@a‐CoOx plate. Furthermore, to clarify the roles of each component, i.e., amorphous cobalt oxides or cobalt phosphides, the CoP particles (CoP‐p) were prepared according to the phosphating process of cobalt chloride while amorphous cobalt oxides (a‐CoOx‐p) were prepared following the procedure of the previous report 11. The powder XRD patterns of CoP‐p and a‐CoOx‐p confirmed the presence of crystalline CoP phase (JCPDS No.…”
Section: Resultsmentioning
confidence: 94%
“…On the CoP and a‐CoOx nanointerfaces, the OH − could preferentially attach to a a‐CoOx site at the interface due to strong electrostatic affinity to the locally positively charged Co 2+ /Co 3+ species and more empty d orbitals in Co 2p than that in CoP, while a nearby CoP site would facilitate H adsorption; suggesting synergistic electrocatalytic activity to CoP@a‐CoOx plate. Furthermore, to clarify the roles of each component, i.e., amorphous cobalt oxides or cobalt phosphides, the CoP particles (CoP‐p) were prepared according to the phosphating process of cobalt chloride while amorphous cobalt oxides (a‐CoOx‐p) were prepared following the procedure of the previous report 11. The powder XRD patterns of CoP‐p and a‐CoOx‐p confirmed the presence of crystalline CoP phase (JCPDS No.…”
Section: Resultsmentioning
confidence: 94%
“…Therefore, special attention has been paid to the development of synthetic methods that enable the composition control with a homogeneous distribution of elements. Such synthesis methods include electrodeposition, [29,93,[150][151][152][153][154][155] photochemical metal-organic deposition (PMOD), [156][157][158][159][160] aerosol-sprayassisted processes, [161,162] reactive magnetron co-sputtering, [163] solvothermal processes, [164] and thermal decomposition. [165] …”
Section: Amorphous Metal Oxidesmentioning
confidence: 99%
“…In addition, Indra et al reported on amorphous Co-Fe oxide catalysts prepared using solvothermal synthesis. [164] The crystallinity of the products was controlled by modifying the solvent type and reaction time of the synthesis process, enabling the formation of both amorphous Co-Fe oxide (CoFe 2 O n , n ≈ 3.66) and crystalline Co-Fe oxide (CoFe 2 O 4 ). With respect to both the mass activity and surface normalized activity, the amorphous Co-Fe oxide (η = 370 mV at 400 mA mg −1 , η = 490 mV at 10 mA cm BET −2 ) exhibited much better performance than its crystalline counterpart (η = 510 mV at 370 mA mg −1 , η = 560 mV at 10 mA cm BET…”
Section: Wwwadvenergymatdementioning
confidence: 99%
“…[32] Spinel oxides (A x B 3−x O 4 ) can be used as bifunctional ORR/OER catalyst in alkaline media. [46] Among spinel oxides, the electron transfer occur with quite low activation energy between the cations of different valences. For example, Chen et al developed a facile and rapid room-temperature method to prepare highly active Co x Mn 3−x O 4 for bifunctional ORR/OER.…”
Section: Mixed-metal Engineeringmentioning
confidence: 99%